A versatile reactive oxygen species‐responsive gels sensor for analysis of metabolic species. Issue 6 (27th October 2020) - Mugo, Samuel M.; Lu, Weihao
Abstract: We report a flexible redox responsive polymer‐based sensor for detection of reactive oxygen species (ROS). The sensor comprises multilayers of silver nanoparticles (AgNPs), carbon nanotube/cellulose nanocrystal (CNT/CNC) and a redox responsive poly (glycidyl methacrylate‐ co ‐ethylene glycol dimethacrylate‐ co ‐vinyl ferrocene), herewith called poly (GMA‐ co ‐EGDMA‐ co Fc) nanoferrogels. These sensor layers were printed on a micropillared polydimethylsiloxane (PDMS) substrate. The nanoferrogel sensor versatility has been demonstrated in its effective detection of ROS species, specifically H2 O2, peroxylipids, and oxidative deriving species such as cholesterol and unsaturated triglycerides. The nanoferrogel ROS sensor rapidly (~1 min) responds to both H2 O2 and peroxylipids with a limit of detection (LOD) of ~0.060 ± 0.001 µg/ml) and 0.012 ± 0.001 µg/ml, respectively. The cholesterol oxidase and lipoxygenase‐based nanoferrogel sensor were successfully evaluated for the detection of cholesterol (LOD of 0.12 ± 0.02 µg/ml) and glyceryltrilinoeate (LOD of 1.8 ± 0.2 ng/ml) standards, respectively. These enzyme‐loaded ROS nanoferrogel sensors were also evaluated for quantification of cholesterol and glyceryltrilinoeate in bacon lard and olive oils. The fabricated flexible ROS sensors are versatile for quantitation of oxidative stress biomarkers, useful in myriad applications including clinical, environmental, food, and plant physiology.